Investigating statistical concepts, applications and methods - Beth L Chance (Duxbury : Brooks/Cole, 2006)
INVESTIGATING STATISTICAL CONCEPTS, APPLICATIONS, AND METHODS (WITH CD-ROM) combines investigation and exposition to explore statistical ideas and techniques. Many of the investigations ask you to use technology such as statistical software and Java applets. A combination of practice, homework, and application problems emphasize actual studies